Zum Transfer kulturspezifischer Textbedeutungen. Theoretische und methodische Überlegungen aus einer semiotischen Perspektive - Hennecke, Angelika (Linguistik Online, 2009)
This paper discusses the role of cultural specific text elements in the constitution of the meaning of the text and focuses the problems which these elements can cause in the translation process. It is based on a description of the translation process as symbiosis of the three categories language, text and culture in a specific situation. The described comprehension of translation turns the question of the methodology of the cultural transfer into a key question that consequently has an impact on the praxis and didactics of translation. The meaning of a text is the result of a complex interaction of different systems in which different types of knowledge are activated. The central question is how culture manifests itself within texts and how these manifestations can be reconstructed, i.e. how the translator's decisions can be made transparent in the context of the transfer. Firstly there is a theoretical reflection on the interdependence of the three categories language, culture and text in which the underlying semiotic conception of text and culture is outlined. On this basis a pragma-semiotic model of the constitution of the text as a complex sign is presented, and a methodology for an integrative text analysis is deduced from this theoretical conception of text constitution. The different forms of cultural specific elements are analyzed and categorized, whereas in addition to the traditional manifestations the concept of intertextuality is introduced and discussed as an important fact for the pragmatic and cultural coherence of the text. The defined forms of cultural specific text elements are illustrated by a number of examples taken from translation praxis and classroom. All the examples are translations from Spanish into German. Finally, the practical and didactical implications, which are of great importance for the training of further translators, are discussed.